Implementing Scientific-Methodological Supervision Through Professional-Pedagogical Associations In The Professional Development Of Teachers (Academicia Review-A Multidisciplinary Online Journal, 2026)
This article examines the pedagogical system of implementing scientific-methodological supervision in the professional development of teachers through professional-pedagogical associations, as well as approaches to improving this process. Based on a comprehensive theoretical and empirical analysis, a model of professional-pedagogical associations is proposed, encompassing diagnostics, the formation of an individual learning pathway, and the integration of modern educational technologies
Keywords: professional development; individualization of teaching; pedagogical system